DEVELOPMENT OF CARBON NANOFIBER/GRAPHENE OXIDE BINARY FILLER-BASED MIXED MATRIX MEMBRANE FOR CO2 AND CH4 PERMEATION - MURUGIAH, PANNIR SELVAM (2018)
Mixed matrix membrane (MMM) is a heterogeneous membrane consisting of inorganic filler embedded in polymer matrix. It combines the desirable properties of both polymeric and inorganic material to form high performance gas separating membrane. Nevertheless, development of MMM is constantly limited by poor dispersion of filler particles in polymer continuous phase, especially when the particles are nano-sized. Moreover, the addition of single filler particles is insufficient to improve the overall membrane permeability and selectivity.